ANALISIS JENIS DAN PEMANFAATAN RADIASI PENGION DI SUMATERA BARAT - Ramacos Fardela; Dedi Mardiansyah; Rani Delvihardini; Rika Analia; Ida Bagus Gede Putra Pratama (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
One important component in the healing effort is the availability of medical equipment needed by patients at the hospital. Completeness of hospital facilities is a support for patient healing and patient comfort. Health care facilities include equipment and human resources. Therefore, this study aims to analyze the type and number of medical imaging equipment against the number of residents and patients in West Sumatra hospitals. The data used in this study are secondary data obtained from the profile of the use of ionizing radiation in the health sector, which comes from BAPETEN and is grouped by field. Hospitals in West Sumatra provide medical equipment in the field of radiodiagnostics with a total of 124 units and radiotherapy with a total of 6 units, but this still shows that the number is still very small compared to the number of residents and patients in West Sumatra so that there are still many patients who feel distress and difficulties in examination and treatment due to being referred to the central hospital. In addition, hospitals in West Sumatra have not yet implemented nuclear medicine equipment even though there are specialist doctors. This is an opportunity for the West Sumatra hospital to be able to develop nuclear medicine so that it can carry out both diagnosis and therapy at the same time with a low number of doses so that it can cure patients.